MODEL FOR PREDICTING RECURRENCE OF INGUINAL HERNIA IN MEN - Andrii Mykhalovuch Prodan (Euromediterranean Biomedical Journal, 2023)
One of the most frequent complications of surgical treatment of inguinal hernias is recurrence. The goal of this research was to develop a mathematical model for predicting the probability of recurrence of inguinal hernias. 54 men were examined for recurrence of inguinal hernia using generally accepted methods. The construction of a prognostic model for the risk of recurrence of inguinal hernia in men was carried out using a multiple regression analysis, considering the following factors: age, period of occurrence of recurrence, type of previous plastic surgery, place of residence (village / city), presence of heart and lung failure. Thus, the quantitative assessment model of existing risk factors and regression analysis for predicting recurrence of inguinal hernias in men, which we have proposed, will allow to reduce the risk of recurrence of inguinal hernias among this cohort of patients with early diagnosis and optimal treatment and prevention tactics.